Reconsidering the Role of Design Standards in Developing Effective Safety Labeling: Monolithic Recipes or Collections of Separable Features?. (September 2019) - Kalsher, Michael J.; Obenauer, William G.; Weiss, Christopher F.
Objective: This research investigated whether safety labeling design guidelines, such as the American National Standards Institute (ANSI) Z535 series, contribute to better warnings. Background: Studies investigating the impact of safety label formatting on warning effectiveness have produced mixed findings. Additionally, research has failed to find a consistent relationship between measures of predicted and actual compliance. One commonality is that all of these studies have investigated the ANSI Z535 guidelines as a binary variable rather than as an integrative system of separable features. Method: We measured predicted compliance using both a within-subjects and a between-subjects design, but actual compliance using only a between-subjects design. Data were analyzed using both analysis of variance and linear/probit regressions to test the relationships between warning features recommended in the ANSI Z535 guidelines and measures of behavioral compliance. Results: Predicted compliance assessed via a within-subjects design differed greatly from predicted compliance assessed via a between-subjects design. Levels of predicted and actual compliance were most similar when both measures were assessed using a between-subjects design. Consistent with previous research, location had a strong relationship with actual compliance, but surprisingly, presence of an ANSI-style orange warning header had a negative relationship with compliance. Conclusion: The choice of experimental design and analytical methods can dramatically influence a study's results and conclusions drawn. This research identified several aspects of experimental design that should be considered in future research on warning effectiveness. Application: Testing features recommended in the ANSI Z535 guidelines under varying conditions can contribute to the development of more effective warnings.